Strategi Komunikasi Pelayanan Publik Dinas Perhubungan Kota Surabaya dalam Edukasi “Andalalin” di Siola Mall - Nabila Rahma Octavia; Laila Khafidah; Afifatur Rohimah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study examines the communication strategy implemented by the Surabaya Transportation Agency in providing education about Traffic Impact Analysis (Andalalin) at Siola Mall with the aim of increasing public understanding and trust in the service. Using a qualitative descriptive approach, data were collected through field observations, activity documentation, and literature studies, then analyzed using the Miles and Huberman model. The findings show that humanely designed communication—prioritizing empathy, information openness, and quality assurance of service—can strengthen the relationship between officers and the community and increase the level of public trust. Communication practices include the delivery of simplified technical information, two-way dialogue to accommodate citizens' aspirations, and demonstrations of transparent Andalalin procedures. Factors that support success include officer competence, consistency of message, and the use of communication media that suits the character of the audience. The obstacles found include initial resistance from the community, limited resources, and the complexity of urban transportation issues. The research recommendations include strengthening the communication capacity of officers, developing participatory educational materials, and cross-sector collaboration to ensure the sustainability of Andalalin's education program and improving the quality of public services in Surabaya.